Strengthening Energy Literacy through Renewable Energy Socialization for Coastal Communities - Pipit Puspitasari; Wahyu Hanaldi; Rizqy Renafasih Alinra; Mardini Hasanah; Chandra Arie Nugrahanto; Sriyatun (TAAWUN, 2026)
This community service program aims to increase understanding and acceptance of renewable energy technology among coastal communities on Bungin Island, Sumbawa Regency, one of the world's most densely populated islands. Despite its enormous solar energy potential, the local community still relies on conventional energy sources, making it economically vulnerable and having a low level of energy security. By applying the Participatory Action Research (PAR) framework, this community service program involved key community stakeholders, including village officials, fishermen's groups, and 20 MSMEs, by conducting a structured three-stage intervention: diagnostic needs assessment through Focus Group Discussions (FGDs), interactive economic literacy education using Levelized Cost of Energy (LCOE) analysis, and direct technical demonstrations of rooftop solar power plants (PLTS). This intervention successfully brought about positive behavioral changes by breaking down psychological barriers related to cost and technological complexity. Specifically, the program empowered local fisheries MSMEs to view renewable energy not as a financial burden but as a strategic asset to reduce production costs and enable “eco-branding” of their products. This activity fostered strong pentahelix collaboration among academics, village governments, and local business groups and built a validated model for the energy transition at the grassroots level. This paper contributes to the literature by providing replicable community engagement strategies to accelerate renewable energy adoption in densely populated, land-constrained island regions, bridging the gap between national energy policy and community readiness.